Caesarean Rates in Brazil: what is Involved?. Issue 1 (March 2016) - de Jesus, G. Ramires; de Jesus, N. Ramires; Peixoto-Filho, F.M.; Lobato, G.
Abstract : (BJOG. 2015;122(5):606–9) Brazil has one of the highest rates of caesarean delivery in the world, reaching rates of >50% for all deliveries in 2012. The current article offers a review of contributory factors to this public health issue, steps that have already been taken to combat it, and suggestions as to how the high cesarean delivery rate in Brazil might be improved.